A Four-Year Descriptive Analysis of Stroke in a Private Hospital in the Western Cape - Govender, Sarojini (Division of General Surgery, 2023)
Background: Stroke is the second leading cause of death and disability globally, with an estimated 26% increase in stroke deaths between 1990 and 2010. The World Stroke Society estimated that one in six people will suffer a stroke in their lifetime. In 2010, stroke accounted for 5.9 million deaths, 71% of which was in low- to middle-income countries (LMICs) and is a major public health concern for Africa and other LMICs together with other non-communicable diseases. Communicable diseases such as HIV/AIDS, malaria, tuberculosis etc. are prioritised in Sub-Saharan Africa (SSA) and the healthcare expenditure has been mostly allocated to treat these. The cost of stroke care in hospital and out of hospital is quite alarming and the burden of stroke places an added burden on an already stretched healthcare budget. Objectives: To identify the different stroke types, risk factors, burden of stroke in a private hospital in terms of gender, age, and length of stay and to identify any associations of risk factors, age, types of strokes, mortality and treatment given. Methods: This descriptive study involved retrospective data from an electronic database which captured all stroke patients seen in the emergency unit during the study period. Data was verified, diagnosis made by CT, MRI scans or both. Results: The total number of 576 cases was included, 278 (48%) for ischaemic stroke, 72(12.5% for haemorrhagic stroke and 226 (39%) for TIA. No difference between gender and type of stroke was observed. Mortality was low, with 21 cases with a mortality rate of 3.6%. Given this low mortality rate, meaningful analyses on mortality could not be done. The most prevalent risk factors were hypertension (59.7%), diabetes (21.7%), hyperlipidaemia (29%), atrial fibrillation (11.1%) and ischaemic heart disease (10.8%). Following logistic regression, atrial fibrillation was found to be associated with ischaemic stroke (p = 0.01), and TIA (p = 0.08). No other risk factors had a statistically significant association with type of stroke in this sample. Conclusion: Ischaemic stroke is more prevalent compared to haemorrhagic stroke. As the population grows and life expectancy increases, the burden of stroke and its complications will also increase. Managing the modifiable risk factors may be key to managing the burden of stroke in Sub-Saharan Africa.